Formulation and Evaluation of Escitalopram Oxalate Oral Films by 32 Factorial Design - Reddy, Gangireddy Ramana; Shankar, Kunderu Ravi; Aminabee, Shaik; Anusha, Ravulapati; Nagaraja, Komanduri Venkata; Haindavi, Borra; Ramitunnisa, Shaik; Babu, Rayavarapu Sanjay; Eswar, Pothuri Srinivasa; Jyothi, Koppula (International Journal of Pharmaceutical Investigation, 2026)
Background The aim of this work was to develop a mouth dissolving film containing Escitalopram oxalate, utilizing basic ingredients such as polymers, plasticizers, sweeteners, saliva-stimulating agents, and flavors, to achieve rapid drug release with good mechanical properties. Materials and Methods The films were prepared using the solvent casting method. Hydroxy Propyl Methyl Cellulose (HPMC) E5 cps was used as the polymer to provide uniform film thickness, while propylene glycol was employed as a plasticizer to enhance folding endurance, tensile strength, and percent elongation. A 3² Factorial Design was utilized to optimize the formulations and assess the influence of variables on film properties. Results and Discussion The optimized formulation (F7) exhibited excellent properties, including good mouth feel, folding endurance, and rapid disintegration. The disintegration time was as short as 20 sec, and 99% of the drug was released within 10 min. These results demonstrated the formulation's potential for immediate drug delivery. Mouth dissolving films of Escitalopram oxalate were successfully developed using HPMC E5 cps and primojel. Conclusion The optimized Formulation (F7) showed promising attributes, such as rapid drug release, satisfactory mechanical properties, and a short disintegration time, making it a suitable candidate for pharmaceutical applications requiring a rapid onset of action.
Keywords: Escitalopram oxalate; HPMC E5; 32 Factorial Design